1991
DOI: 10.1055/s-2007-1025390
|View full text |Cite
|
Sign up to set email alerts
|

Die Myokarditis im Kindesalter

Abstract: Infectious heart diseases in childhood are--with less than 1% of hospital admissions--rare, but serious diseases. Among several causes of myocarditis in our region virus myocarditis plays the most important role. Besides of the acute course an autoimmune mediated chronic myocarditis and the transition to dilated cardiomyopathy are observed. The patho-histological assessment depends also on subjective influences. Clinical diagnosis is based on cardiac symptoms (Adams-Stokes, congestive heart failure, LV-dilatat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

1992
1992
2001
2001

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…However, in earlier years, we did not have the methodologic tools to differentiate among different types of myocarditis. More recently, our own meta-analysis of childhood myocarditis [17], and an overview for the adult age by Maisch et al [12], showed no superiority of immunosuppressive therapy. This may be because in the past we were not able to distinguish between chronic myocarditis with persistent viral infection and autoimmune-triggered chronic myocarditis.…”
Section: Discussionmentioning
confidence: 97%
“…However, in earlier years, we did not have the methodologic tools to differentiate among different types of myocarditis. More recently, our own meta-analysis of childhood myocarditis [17], and an overview for the adult age by Maisch et al [12], showed no superiority of immunosuppressive therapy. This may be because in the past we were not able to distinguish between chronic myocarditis with persistent viral infection and autoimmune-triggered chronic myocarditis.…”
Section: Discussionmentioning
confidence: 97%
“…Key words: myocarditis ± infancy and childhood ± pathogenesis ± treatment Einleitung Vor 10 Jahren publizierte der Erstautor in dieser Zeitschrift einen Übersichtsartikel über die Myokarditis im Kindesalter [50]; seitdem ist das Wissen über diese Erkrankung soviel gründlicher und umfassender geworden, dass es sich lohnt, einen Überblick über diesen Fortschritt zu geben, aber auch die noch offenen Fragen zu stellen und zur Mitarbeit an einer multizentrischen Therapiestudie aufzurufen.…”
unclassified